CRANIOTOPOGRAPHIC CHARACTERISTICS OF VENOUS-LIQUOR RELATIONSHIPS IN THE SAGITTAL PLANE - Bondarenko, S.V.; Dubyna S.О.; Serbin, S.I.; Khapchenkova, D.S.; Koptev М.М.; Sovgyria S.М.; Danylchenko S.І. (World of Medicine and Biology, 2023)
This study was performed on 100 corpses of people of different ages and gender with the manufacturing of native preparations of the brain with membranes and liquor structures. Of the specified number of morphological objects, 70 preparations of veins and sinuses of the dura mater of the brain and 30 preparations of the cerebrospinal fluid system of the brain of adults were made. We used such research methods as: macro – and micropreparation of anatomical objects of the brain; cranio – and morphometry of veins, sinuses of the dura mater of the brain and liquor structures of the brain; manufacturing of corrosive (acrylic) casts-preparations of veins, sinuses of the dura mater of the brain and liquor formations of the brain; injection technique; variational-statistical analysis of morphometric data; computer-graphic analysis. The craniotopographic (metric) indicators of venous-liquor relationships in the sagittal plane obtained by us can be used to substantiate the insertion of a puncture needle into the cavity of the lateral ventricles or their departments, based on the maximum allowable depth of its insertion.